2015
DOI: 10.1890/14-1735.1
|View full text |Cite
|
Sign up to set email alerts
|

Hunting alters seedling functional trait composition in a Neotropical forest

Abstract: Abstract. Defaunation alters trophic interactions between plants and vertebrates, which may disrupt trophic cascades, thereby favoring a subset of plant species and reducing diversity. If particular functional traits characterize the favored plant species, then defaunation may alter community-wide patterns of functional trait composition. Changes in plant functional traits occurring with defaunation may help identify the species interactions affected by defaunation and the potential for other cascading effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 36 publications
(53 reference statements)
5
62
2
1
Order By: Relevance
“…S4) (20, 23), suggesting that overhunting-induced reductions in seedling recruitment are disproportionately stronger in heavy-wooded tree species. These patterns are corroborated by studies in Mesoamerica (11,15), Africa (13,14,43,44), and southern Asia (12), showing that severe depletion of large frugivores negatively affects the recruitment, relative abundance, and population growth rate of large-seeded trees. However, our simulations may conservatively exclude some very large-seeded species (typically with seed lengths >45 mm) from our list of candidate taxa projected to undergo severe dispersal limitation, even though these species are often associated with high wood density (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…S4) (20, 23), suggesting that overhunting-induced reductions in seedling recruitment are disproportionately stronger in heavy-wooded tree species. These patterns are corroborated by studies in Mesoamerica (11,15), Africa (13,14,43,44), and southern Asia (12), showing that severe depletion of large frugivores negatively affects the recruitment, relative abundance, and population growth rate of large-seeded trees. However, our simulations may conservatively exclude some very large-seeded species (typically with seed lengths >45 mm) from our list of candidate taxa projected to undergo severe dispersal limitation, even though these species are often associated with high wood density (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Our findings highlight that global declines in vertebrate populations (14-17) could significantly impact forest regeneration through reducing seed dispersal. While Guam represents an extreme case of complete disperser loss, leading to gap seedling richness being approximately halved and seedling turnover among gaps being doubled, other studies have demonstrated that partial loss of dispersers can reduce seedling diversity and disproportionally alter species abundances (20,23,45), particularly of light-demanding pioneer species (22,46). While we have to wait to see how gap dynamics play out in the presence and absence of dispersers on these islands, our findings show that global vertebrate losses have the potential to profoundly alter tropical forest composition.…”
Section: Resultsmentioning
confidence: 99%
“…Key issues here are that even high hunting pressure has not led to the complete loss of vertebrate dispersers (e.g., ref. 14); hunting also removes vertebrate seed predators and seedling browsers (20,22,23), making it difficult to isolate an effect of seed disperser loss alone; and the treatment of interest (removal of vertebrate dispersers) can be confounded with other site differences. Hunting pressure, for example, is often higher in areas without formal conservation protection, meaning these areas experience additional human pressures that affect tree populations, such as forest fragmentation and tree harvesting (14,20,24,25).…”
mentioning
confidence: 99%
“…Part of this complexity is evident in the vertical stratification of different faunal communities between terrestrial and canopy layers [3][4][5][6][7]. Research suggests that arboreal rainforest mammal species should be high conservation priorities because habitat alteration due to anthropogenic activities causes a greater disruption to arboreal than to terrestrial biodiversity [4,[7][8][9][10][11] and, as with rainforest mammals in general, they are often prey to human disturbance in the form of hunting.…”
Section: Introductionmentioning
confidence: 99%